2012
DOI: 10.1371/journal.pone.0046209
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Hydroxylase from Legionella pneumophila Is a Thermostable Enzyme with a Major Functional Role in Pyomelanin Synthesis

Abstract: Background Legionella pneumophila is a pathogenic bacterium that can cause Legionnaires’ disease and other non-pneumonic infections in humans. This bacterium produces a pyomelanin pigment, a potential virulence factor with ferric reductase activity. In this work, we have investigated the role of phenylalanine hydroxylase from L. pneumophila (lpPAH), the product of the phhA gene, in the synthesis of the pyomelanin pigment and the growth of the bacterium in defined compositions.Methodology/Principal FindingsComp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 80 publications
2
63
1
Order By: Relevance
“…1) (46-49). It has been shown that an abundance of either tyrosine or phenylalanine in the medium increases pigment production (50) and that conversion of Phe into Tyr by the phenylalanine hydroxylase (PAH; Fig. 1) provides the excess Tyr needed to produce the pigment (50).…”
Section: Resultsmentioning
confidence: 99%
“…1) (46-49). It has been shown that an abundance of either tyrosine or phenylalanine in the medium increases pigment production (50) and that conversion of Phe into Tyr by the phenylalanine hydroxylase (PAH; Fig. 1) provides the excess Tyr needed to produce the pigment (50).…”
Section: Resultsmentioning
confidence: 99%
“…are expressed in L. pneumophila biofilms and in Legionella-infected macrophages and the pigment is seen in L. pneumophilainfected lungs and sputum (6,31,(45)(46)(47). That nonpigmented mutants are still able to grow in amoebae and macrophage host cells (28,30,36) is compatible with the fact that the bacterium has multiple means of iron uptake.…”
Section: Figmentioning
confidence: 94%
“…In order to construct the lbtA lly double mutant NU424, plasmid pUClly::GNT (31) was introduced into the lbtA mutant NU302 by transformation. Transformants were selected on antibiotic-containing agar medium, and insertion of the gentamicin resistance cassette into the lly gene was confirmed by PCR using primers llyLpgFBcl1 and llyLpgXho1, as previously described (31). Escherichia coli strain DH5␣ (Invitrogen, Carlsbad, CA) was used as the host for recombinant plasmids.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations